Negative pattern generation technique by laser beam writing for integrated optics - Park, KH; Kim, MW; Byun, YT; Kim, SH; Cho, WR; Park, SH; Kim, U; Choi, SS (JAPAN J APPLIED PHYSICS, 1998)
A novel technique for fabricating negative tone patterns fur waveguide devices, using laser beam writing is proposed. An optoelectronic device pattern with good contrast and a smooth curve is generated. Our proposed technique can extend the applications of laser beam writing to the fabrication of the optoelectronic devices.